If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(10x + 2) = 11 Reorder the terms: x(2 + 10x) = 11 (2 * x + 10x * x) = 11 (2x + 10x2) = 11 Solving 2x + 10x2 = 11 Solving for variable 'x'. Reorder the terms: -11 + 2x + 10x2 = 11 + -11 Combine like terms: 11 + -11 = 0 -11 + 2x + 10x2 = 0 Begin completing the square. Divide all terms by 10 the coefficient of the squared term: Divide each side by '10'. -1.1 + 0.2x + x2 = 0 Move the constant term to the right: Add '1.1' to each side of the equation. -1.1 + 0.2x + 1.1 + x2 = 0 + 1.1 Reorder the terms: -1.1 + 1.1 + 0.2x + x2 = 0 + 1.1 Combine like terms: -1.1 + 1.1 = 0.0 0.0 + 0.2x + x2 = 0 + 1.1 0.2x + x2 = 0 + 1.1 Combine like terms: 0 + 1.1 = 1.1 0.2x + x2 = 1.1 The x term is 0.2x. Take half its coefficient (0.1). Square it (0.01) and add it to both sides. Add '0.01' to each side of the equation. 0.2x + 0.01 + x2 = 1.1 + 0.01 Reorder the terms: 0.01 + 0.2x + x2 = 1.1 + 0.01 Combine like terms: 1.1 + 0.01 = 1.11 0.01 + 0.2x + x2 = 1.11 Factor a perfect square on the left side: (x + 0.1)(x + 0.1) = 1.11 Calculate the square root of the right side: 1.053565375 Break this problem into two subproblems by setting (x + 0.1) equal to 1.053565375 and -1.053565375.Subproblem 1
x + 0.1 = 1.053565375 Simplifying x + 0.1 = 1.053565375 Reorder the terms: 0.1 + x = 1.053565375 Solving 0.1 + x = 1.053565375 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1' to each side of the equation. 0.1 + -0.1 + x = 1.053565375 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + x = 1.053565375 + -0.1 x = 1.053565375 + -0.1 Combine like terms: 1.053565375 + -0.1 = 0.953565375 x = 0.953565375 Simplifying x = 0.953565375Subproblem 2
x + 0.1 = -1.053565375 Simplifying x + 0.1 = -1.053565375 Reorder the terms: 0.1 + x = -1.053565375 Solving 0.1 + x = -1.053565375 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.1' to each side of the equation. 0.1 + -0.1 + x = -1.053565375 + -0.1 Combine like terms: 0.1 + -0.1 = 0.0 0.0 + x = -1.053565375 + -0.1 x = -1.053565375 + -0.1 Combine like terms: -1.053565375 + -0.1 = -1.153565375 x = -1.153565375 Simplifying x = -1.153565375Solution
The solution to the problem is based on the solutions from the subproblems. x = {0.953565375, -1.153565375}
| 2(8+n)=16+8 | | Y+23=7 | | 33/x=21/23 | | x^2-2x+16=14.875 | | 24x^2+34x+12=0 | | 2.6=2x/0.3-x | | 3/5(x-4)-2/3(4-5x) | | Y-4=1+1 | | logx-log(3x+5)=-2 | | 69-m=267 | | 5m+2=m+2 | | 18x^4-128= | | -13+2-11= | | (3p-5)(p-2)=0 | | 292=-m+197 | | 4x^2+x=7 | | (8b+1)(b+8)=0 | | 8b^2-48b=0 | | Y^3-29yn^3+19y^3n^5-29y^3n^3= | | 3k-4+k+8-2k-1= | | 44/14 | | -w+178=16 | | (v+8)(2v-5)=0 | | -13+2x-11= | | 2(22/7) | | 4=3x+8 | | F-2=13 | | -(2x^-4y^-1/-8x^2y^-4) | | 12=6+2x | | 27+2y-9=9y-12-2y | | 4x+5-7=4x+3-X | | 4p-7=3p+9 |